Pengaruh Pajak Cryptocurrency Terhadap Keputusan Investasi dengan Moderasi Literasi Keuangan - Nanda Wahyu Saputra; Rida Perwita Sari (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effect of cryptocurrency tax collection on cryptocurrency investment decisions in Indonesia moderated by financial literacy. The population of this study consists of cryptocurrency investors in Indonesia. This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) assisted by SmartPLS 4 software. Sampling was conducted using a simple random sampling technique, and data were obtained through distributing questionnaires to 118 respondents through Slovin formula sampling measurement technique with a 10% error rate (it was found that the minimum number of respondents required was 100 respondents). The results show that cryptocurrency tax collection has a positive and significant effect on investment decisions. This indicates that the existence of taxes is not only perceived as a burden, but also as a factor that increases legitimacy and investor confidence in investing. Meanwhile, financial literacy was not proven to significantly moderate the effect of cryptocurrency tax collection on cryptocurrency investment decisions, although investors with higher financial literacy tend to consider various investment aspects more rationally. These findings provide theoretical implications that tax policy can be viewed not only as a transaction burden, but also as a form of legitimacy that influences cryptocurrency investment decisions. Practically, the results of this study can serve as input for the government in designing tax policies that are able to increase investor confidence and support the development of the cryptocurrency investment ecosystem in Indonesia.